Water Management as A Key Nutrient for Broiler Chickens Performance at CV. Berkah Putra Chicken - R. Susilowarno; D. A. Astuti; Sumiati; R. Fadhilah (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
Water is one of the essential nutritional components that is very important in broiler chicken maintenance. Chicken drinking water consumption can indicate health or good/bad maintenance management practices. Causes of decreased water consumption include chickens being infected with a disease, environmental conditions that are too cold, uneven number and distribution of drinking places, dirty chicken drinking places, and poor water quality, especially seen from the physical water (clarity and color of the water). Observations were made by collecting data through direct observation in the field with data collection instruments in the form of observation and interviews. Observations were carried out by collecting data through direct observation in the field with data collection instruments in the form of observation, interviews and variables measured, namely testing drinking water for chickens, body weight (g/head), feed consumption (g/head), depletion (%) feed conversion, performance index and profit. Observation resultsshowed that water quality and quantity were proven to have a significant impact on chicken productivity according to the age and body weight of the chicken. The results obtained after water treatment were that the E.coli and salmonella levels in nipple water were below the E.coli standard <50/ml Salmonella <0/ml and the performance index obtained at the Mansur farm was 501, the Khomer farm was 413 and the palm oil farm was 471 as well as profits produced with good water quality is greater IDR. 8,623 per head, while water quality that is not good gets a smaller profit of IDR 1,973/chicken.